Comparative physiological, transcriptomic, and WGCNA analyses reveal the key genes and regulatory pathways associated with drought tolerance in Tartary buckwheat - Meng, Heng-Ling; Sun, Pei-Yuan; Wang, Jia-Rui; Sun, Xiao-Qian; Zheng, Chuan-Zhi; Fan, Ting; Chen, Qing-Fu; Li, Hong-You (Frontiers in Plant Science, 2022)
Drought stress is one of the major abiotic stress factors that affects plant growth and crop productivity. Tartary buckwheat is a nutritionally balanced and flavonoid-rich pseudocereal crop and also has strong adaptability to different adverse environments including drought. However, little is known about its drought tolerance mechanism. In this study, we performed comparative physiological and transcriptomic analyses of two contrasting drought-resistant Tartary buckwheat genotypes under nature drought treatment in the reproductive stage. Under drought stress, the drought-tolerant genotype XZSN had significantly higher contents of relative water, proline and soluble sugar, as well as lower relative electrolyte leakage in the leaves than the drought-susceptible LK3. A total of 5,058 (2,165 up-regulated and 2,893 down-regulated) and 5,182 (2,358 up-regulated and 2,824 down-regulated) potential drought response genes were identified in XZSN and LK3 by transcriptome sequencing analysis, respectively. Among the potential drought response genes of XZSN, 1,206 and 1,274 genes were identified to be the potential positive and negative contributors for XZSN having higher drought resistance ability than LK3. Furthermore, 851 out of 1,206 positive drought-resistance genes were further identified to be the core drought-resistance genes of XZSN based on WGCNA analysis, and most of them were induced earlier and quicker by drought stress than those in LK3. Functional annotation of the 851 core drought-resistance genes found that a large number of stress response genes were involved in TFs, ABA biosynthesis, signal transduction and response, non-ABA signal molecules biosynthesis, water holding, oxygen species scavenging, osmotic adjustment, cell damage prevention, and so on. Transcriptional regulatory network analyses identified the potential regulators of these drought-resistance functional genes and found that the HD-ZIP and MYB TFs might be the key down-stream TFs of drought-resistance in Tartary buckwheat. Taken together, these results indicated that XZSN genotype was more drought-tolerant than LK3 genotype as evidenced by triggering the rapid and dramatic transcriptional reprogramming of drought-resistance genes to reduce water loss, prevent cell damage, and so on. This research expands our current understanding of the drought tolerance mechanisms of Tartary buckwheat and provides important information for its further drought-resistance research and variety breeding.